Pengaruh Kualitas Pelayanan Dan Promosi Terhadap Kepuasan Konsumen Pada Fitri Rias Di Ranca Iyuh Tangerang Banten - Siti Nurpadilah; Renny Anggraini (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This research aims to find out how much influence Service Quality and Promotion has on Consumer Satisfaction at Fitri Rias in Ranca Iyuh Tangerang Banten Partially or Simultaneously. The method used by researchers is a quantitative method. The population in this study were all consumers at Fitri Rias Ranca Iyuh Tangerang Banten. The sample collection technique used the Slovin formula which obtained a sample of 60 respondents. This research uses a questionnaire as a data collection tool. The data analysis method used is multiple linear regression analysis. The research results show that the value of tcount > t table (6.183 > 2.001) with a significance level of (0.000<0.050) which means that Service Quality has a positive and significant effect on Consumer Satisfaction. The calculated t value > t table (3.707 > 2.001) with a significance level of (0.000<0.050) which means that promotion has a positive and significant effect on consumer satisfaction. Apart from that, service quality and promotion simultaneously influence consumer satisfaction. This can be seen based on the calculated F value > F table (25.682 > 3.160) with a significance level of (0.000 < 0.050). With the multiple linear regression equation Y= 16.004+0.442X1+0.267X2